The effect of habitat and climatic on microsatellite diversity and allele length variation - Cohen, Orly; Ram, Yoav; Hadany, Lilach; Geffen, Eli; Gafny, Sarig (Frontiers in Ecology and Evolution, 2022)
Microsatellite loci have been shown to vary according to environment. We studied allelic length variation and diversity in eight microsatellite loci along a sharp climatic and habitat gradient in Israel, using the eastern spadefoot toad (Pelobates syriacus) as our model system. We found a gradual increase in allele lengths from north to south. We used a distance-based redundancy analysis (dbRDA) to associate between allele length and habitat and climatic measures and found that geography and annual climate explained the significant variation in allele length. We also used additional measurements pertaining to demography, heterozygosity and allelic diversity to explore four different hypotheses that might explain the variations in allele length. Our results suggest that the changes we observed in allele lengths may not be purely random but could be influenced by the differential mutation rate and/or local environmental conditions operating at the different locations.